2016
DOI: 10.4040/jkan.2016.46.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physical Health in Family Caregivers of Intensive Care Unit Survivors: Current Knowledge and Future Research Strategies

Abstract: Purpose: This article provides an overview of current knowledge on the impact of caregiving on the psychological and physical health of family caregivers of intensive care unit (ICU) survivors and suggestions for future research. Methods: Review of selected papers published in English between January 2000 and October 2015 reporting psychological and physical health outcomes in family caregivers of ICU survivors. Results: In family caregivers of ICU survivors followed up to five years after patients' discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
0
34
0
3
Order By: Relevance
“…The current study adds new information regarding family members' suggestions for helpful follow‐up strategies, including offering telephone calls after a few weeks, providing the opportunity to clarify information or participating in re‐visits to the ICU to help in handling problems. The nurses' unique position to provide insight and support to family members during the stay and to help them be aware of their own physical health, is important to prevent post‐ICU vulnerability (Choi, Donahoe, & Hoffman, ). Family member' follow‐up needs after ICU experiences, require further investigation to determine the most suitable support system.…”
Section: Discussionmentioning
confidence: 99%
“…The current study adds new information regarding family members' suggestions for helpful follow‐up strategies, including offering telephone calls after a few weeks, providing the opportunity to clarify information or participating in re‐visits to the ICU to help in handling problems. The nurses' unique position to provide insight and support to family members during the stay and to help them be aware of their own physical health, is important to prevent post‐ICU vulnerability (Choi, Donahoe, & Hoffman, ). Family member' follow‐up needs after ICU experiences, require further investigation to determine the most suitable support system.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the respondents had experienced unpleasant physical, psychological, or social experiences while caregiving. The result of a review showed that sleep disorders, fatigue, and inadequate self-care were recognized as common physical health problems in family caregivers [36]. Family caregivers may also grapplewith anxiety, depression, apathy, disappointment, loneliness, and isolation because of reduced social interactions and social exclusion while providing that care [19,37].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, a critical illness that requires admission to an ICU is associated with high-intensity situational and environmental stress. Family caregivers experience negative psychological responses, such as anxiety, depressive symptoms, and post-traumatic stress, that persist even after the patient is discharged from the ICU (Carlson et al, 2015; Choi et al, 2016; Johnson et al, 2019; McAdam et al, 2012). These negative psychological responses may affect family caregivers’ ability to make decisions on behalf of patients (Bolosi et al, 2018; Loghmani et al, 2014; McAdam et al, 2012), maintain their personal physical and mental health, and continue their caregiving role after the patients’ ICU discharge (Cameron et al, 2016; Turner-Cobb et al, 2016).…”
Section: Introductionmentioning
confidence: 99%